THE IMPLEMENTATION OF TRAINING-COACHING-INSPIRING MODEL IN MANAGERIAL TRAINING AND EVALUATION OF ENGLISH BASED INSTITUTIONS - Khairun Nisa; Neni Afrida Sari Harahap (PT. Intelek Cendikiawan Nusantara, 2025)
This study aimed at investigating the aspects and phases of Training-Coaching-Inspiring (TCI) Model in managerial training and evaluation of English Based Institution. It was a case study at HERO English Course Medan. The research employed a qualitative case study method which was focusing on a single informant the academic manager at HERO English Course in Medan, Indonesia. Data were collected through semi-structured interviews and document analysis. The findings revealed that HERO applies a structured three-phases training model known as